Rancang Bangun Sistem Auto-Config Sensor Baru pada Perangkat IoT secara Over-The-Air menggunakan Protokol HTTP berbasis Raspberry-Pi - Syahrul Ramadhan; Agung Setia Budi; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Sometimes there is the addition of new sensors on IoT devices to suit the needs of the environment, which will take time or spend a lot of time manually configuring each device. If the device is already connected to network communication, the configuration can be done Over-The-Air. By using the HTTP protocol and the Rest-Api concept, the device can auto-config the firmware when a new sensor is installed. The device will make a configuration request according to the sensor read by it, and the server will return the required configuration, once it is received, the device will automatically process it into firmware for the sensor. From the tests carried out 90 times with details, namely there are 3 types of sensors, 10 trials of each sensor, and carried out at 3 different distances, namely 4-meters, 8-meters, and 12-meters, the average delay of the auto-processing process was obtained. The config on the LM75A sensor experiment with a distance of 4,8 and 12-meters is 10198 ms, 10204 ms, and 12019 ms, respectively. In the experiment the SW420 sensor with a distance of 4,8 and 12-meters is 9700 ms, 9802 ms, and 9819 ms, respectively. In the RAIN sensor experiment with 4,8 and 12-meter distances, they were 9708 ms, 9629.9 ms, and 9815 ms, respectively.